2013
DOI: 10.1063/1.4789908
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the performance of InAs quantum dots solar cell by surface modification using Poly-L-Lysine homopolymers

Abstract: Articles you may be interested inSuppression of thermal carrier escape and efficient photo-carrier generation by two-step photon absorption in InAs quantum dot intermediate-band solar cells using a dot-in-well structure J. Appl. Phys. 116, 063510 (2014); 10.1063/1.4892826 Effect of quantum dot position and background doping on the performance of quantum dot enhanced GaAs solar cells Appl. Phys. Lett.High-efficiency InAs/GaAs quantum dot solar cells by metalorganic chemical vapor deposition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Non-conjugated electrolytes are also usually functionalized with charged pendant parts such as amino-functionalized groups, similar to the widely used conjugated CIMs. Non-conjugated polymer electrolytic materials, such as polyethyleneimine (PEI), poly-ethyleneimine-ethoxylated (PEIE), and poly-amino acid α-poly- l -lysine, which were deposited on top of metals or ITO via spin coating and low-temperature processing, can form dipoles between the photoactive layers and the cathodes and effectively reduce the WFs of the cathodes. , However, recent studies have shown that some non-fullerene-based OSCs with the interfacial materials with amino groups (e.g., PEI and PEIE) exhibited “S” shaped J – V curves under illumination, indicating that the charge extraction in the devices is not efficient possibly due to the adverse interactions between the ITIC-based non-fullerene acceptor and the PEI or PEIE interlayers . Consequently, the original electronic structure of the acceptor is destroyed, leading to lower device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Non-conjugated electrolytes are also usually functionalized with charged pendant parts such as amino-functionalized groups, similar to the widely used conjugated CIMs. Non-conjugated polymer electrolytic materials, such as polyethyleneimine (PEI), poly-ethyleneimine-ethoxylated (PEIE), and poly-amino acid α-poly- l -lysine, which were deposited on top of metals or ITO via spin coating and low-temperature processing, can form dipoles between the photoactive layers and the cathodes and effectively reduce the WFs of the cathodes. , However, recent studies have shown that some non-fullerene-based OSCs with the interfacial materials with amino groups (e.g., PEI and PEIE) exhibited “S” shaped J – V curves under illumination, indicating that the charge extraction in the devices is not efficient possibly due to the adverse interactions between the ITIC-based non-fullerene acceptor and the PEI or PEIE interlayers . Consequently, the original electronic structure of the acceptor is destroyed, leading to lower device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Although both panels have output energy reduction, the coated panels are still superior to the uncoated panels. This can be attributed to the fact that hydrophobic surfaces have less surface tension, therefore reducing the tendency for dust particles to stick on the coated surface [25][26][27][28][29][30]. Therefore, less dust accumulation is achieved, making this method an excellent choice for dusty areas.…”
Section: Daily Generated Energy Between Two Cleaning Cyclesmentioning
confidence: 99%
“…As new platforms for water solubilizers, we focused on polypeptides due to their excellent biocompatibility, biodegradability, thermal stability, and functionality. [23][24][25][26][27][28][29][30][31][32][33][34] More recently, using polypeptides as solubilizers, we succeeded in solubilizing paclitaxel, a hydrophobic anticancer drug, in larger quantities compared to that using polysaccharides, which are conventional solubilizers. 35 The results encouraged us to investigate the applicability of polypeptides as water solubilizers.…”
Section: Introductionmentioning
confidence: 99%
“…With an excellent biocompatibility [23][24][25][26][27][28][29][30][31][32][33][34][35] and responsiveness to external stimuli, including enzymes, 23,24 pH, 25,26 and reactive oxygen species, 27 polypeptides have been used in various elds, including the biomedical eld, as drug delivery systems 23,27,29 and hydrogels. 24,[27][28][29] For example, poly-L-lysine (PLL), which is traditionally used as a coating agent for culture media to enhance the attachment of cells 30 and manipulate neuronal cellular fate, 31 has a primary amino group in its side chain, which contributes to structural changes associated with pH changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation